Processing method of multilayer circuit board
Through segmented coating and thermal curing technology, the insulating layer and conductive lines are stacked layer by layer, solving the problem of poor thickness uniformity and flatness between multi-layer circuit boards, and achieving higher mechanical strength and durability.
Patent Information
- Application Number
- CN202510325881.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-19
- Publication Date
- 2025-04-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In the existing multi-layer circuit board process, poor interlayer thickness uniformity and poor overall flatness lead to large plate thickness deviations and bending or warping problems.
The copper foil is coated and thermally cured by using the method of segmented coating and layered coating of insulating coating to form a glue-backed copper foil, and the insulating layer and conductive lines are stacked layer by layer through vacuum bonding and thermal curing technology.
It significantly improves the interlayer thickness uniformity and overall flatness of the multi-layer circuit board, reduces dimensional deviations caused by stress, and enhances the mechanical strength and durability of the board.
Smart Images

Figure CN119855073A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of semiconductor packaging, and in particular relates to a processing method of a multi-layer circuit board. Background Art
[0002] The traditional circuit board stacking process uses the method of "inner layer circuit → prepreg + copper foil stacking → vacuum / hot pressing → outer layer circuit processing" to achieve mass production of multi-layer circuit boards. This method has long been the mainstream in PCB manufacturing due to its high maturity and low material cost. However, in advanced applications such as high layer count, ultra-thin dielectric, and high-density circuits, it has the following defects.
[0003] On the one hand, the prepreg is usually made of glass fiber cloth impregnated with resin and then dried. Affected by the fiber weaving density and the amount of resin coating, the sheet itself has a certain thickness tolerance, which makes it difficult to be extremely thin or extremely uniform. After stacking multiple layers, these tiny tolerances will accumulate, resulting in a large deviation in the overall thickness of the board and poor uniformity in thickness between layers. On the other hand, the expansion coefficient and strength of glass fiber cloth in different directions are not consistent. After high-temperature pressing, it may produce thermal stress differences with the inner copper foil or substrate, causing the overall board to bend or warp. Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide a processing method for a multi-layer circuit board, aiming to solve the problems of poor thickness uniformity between layers and poor overall flatness of the multi-layer circuit board.
[0005] To solve the above technical problems, the present invention is implemented as follows: a method for processing a multi-layer circuit board, the steps comprising: S1. Surface treating the copper foil raw material to obtain a roughened copper foil; S2. preparing an insulating coating, wherein the insulating coating comprises a base layer coating and a functional layer coating; S3, sequentially coating at least one of the base layer coating and at least one of the functional layer coating on the rough surface of the roughened copper foil, performing a staged curing after each coating to form an insulating layer, and obtaining a self-adhesive copper foil, wherein the self-adhesive copper foil includes a copper layer connected to the insulating layer; S4, vacuum-bonding the insulating layer of the adhesive-backed copper foil to the substrate, etching the copper layer to form a conductive circuit, and repeating at least one adhesive-backed copper foil bonding and etching step within the required number of layers to obtain a multi-layer circuit board.
[0006] In some embodiments of the present invention, step S1 comprises: S1.1, prepare a cleaning solution, the cleaning solution includes a weak alkaline solvent and a surfactant, the pH value of the cleaning solution is 9-11, and the cleaning solution is heated to 40-60°C; S1.2. Circulate the cleaning solution, place the copper foil raw material in the cleaning solution, soak for 1 to 3 minutes, take it out, rinse it with pure water and then dry it; S1.3, the dried copper foil raw material is placed in an acidic solution including sulfuric acid and chloride-containing salt, heated to 25-45°C for roughening, and maintained for 0.5-1.5 minutes. The roughened copper foil raw material is rinsed with multi-stage pure water and dried to obtain a roughened copper foil.
[0007] In some embodiments of the present invention, in step S2, the base layer coating comprises a base resin, a crosslinking agent, a toughening agent, and a leveling agent, the base resin comprises at least one of epoxy resin, polyimide, and phenolic resin, the crosslinking agent comprises at least one of 4,4'-diaminodiphenylmethane, polyethylene polyamine, dicyandiamide, methyltetrahydrophthalic anhydride, maleic anhydride, methyl anhydride, and segmented urea-formaldehyde resin, the toughening agent comprises at least one of carboxyl-terminated nitrile rubber, polyether sulfone, and polyaryl sulfone, The functional layer coating comprises a functional resin, a nano-composite filler, a curing agent, and a coupling aid. The functional resin comprises at least one of an epoxy resin containing amino / hydroxyl groups, a benzoxazine resin, and a thermosetting acrylic copolymer resin. The nano-composite filler comprises at least one of a zinc oxide-graphene composite powder, an aluminum oxide-carbon nanotube composite powder, a silicon dioxide-graphene composite powder, and a titanium dioxide-graphene composite powder. The curing agent comprises at least one of 4,4'-diaminodiphenyl ether, methyl anhydride, and a cyclohexylamine derivative. The coupling aid comprises at least one of γ-aminopropyltriethoxysilane, a titanate coupling agent, and a zirconate coupling agent.
[0008] In some embodiments of the present invention, step S3 includes: S3.1, setting the coating speed to 1-8 m / min, coating the base layer coating on the rough surface of the roughened copper foil, and controlling the gap accuracy between the lip of the coating head and the roughened copper foil to be within 10-20 μm; S3.2, heat to 50~60℃, keep warm for 2~3min, then heat to 100~120℃, keep warm for 5~10min, and cool to room temperature after heating; S3.3, an ultrasonic dispersing unit is arranged in front of the coating head to disperse the functional layer coating while conveying, and the functional layer coating is coated on the surface of the cured base layer coating, and the thickness of the functional layer coating is controlled to be 30-50 μm; S3.4, heat to 120~140℃, keep warm for 10~30min, and cool to room temperature after heating; S3.5, repeating steps S3.1 to S3.4 according to the preset number of layers to form an insulating layer and obtain a copper foil with adhesive backing.
[0009] In some embodiments of the present invention, the base layer coating comprises a first photoinitiator, the functional layer coating comprises a second photoinitiator, and before step S3.2, the following steps are further included: The base layer coating is irradiated with a scanning light source with a wavelength of 365-385 nm, a moving speed of 0.2-0.33 m / s, a scanning power of 50-100 mW / cm², and maintained for 30-120 seconds; Before step S3.4, the method further includes: The functional layer coating is irradiated with a light source having a wavelength of 405-420 nm and a power of 200-300 mW / cm² for 5-10 seconds.
[0010] In some embodiments of the present invention, the first photoinitiator includes at least one of benzoin ether, 2-hydroxy-2-methyl-1-phenylpropanone, and 1-hydroxy-cyclohexyl phenyl ketone, and the second photoinitiator includes at least one of 2,4,6-trimethylbenzoyl) (dimethylamino) phenyl phosphine oxide, (2-phenylpropionyl) triphenyl phosphine oxide derivatives, and 2,4,6-trimethylbenzoyl diphenyl phosphine oxide.
[0011] In some embodiments of the present invention, step S2 includes: S2.1. Add solvent and base resin into the reaction tank, control the stirring temperature at 40-60°C, and keep stirring for 15-30 minutes; S2.2, after the viscosity of the system changes less than the preset range, add the crosslinking agent, stir for 5-10 minutes, then add the toughening agent and leveling agent, and continue stirring for 10-15 minutes; S2.3, the temperature is lowered to below 40°C, the first photoinitiator is slowly added, and stirring is continued for 10 minutes to obtain a first mixture, the viscosity of the first mixture is controlled within the first viscosity range, the first mixture is transferred to a vacuum degassing tank, maintained at -0.08MPa, degassed for 5 to 10 minutes, and the base layer coating is obtained after cooling to room temperature; S2.4, ultrasonically disperse the nanocomposite raw material in a small amount of acetone or ethanol for 10 to 20 minutes, add part of the coupling agent, stir for 5 to 10 minutes, and dry at low temperature to obtain a nanocomposite filler; S2.5, adding functional resin and part of solvent into a stirring tank, heating to 50-60°C, adding curing agent and stirring for 10-15 minutes, slowly adding the nanocomposite filler into the stirring tank, and continuously dispersing for 10-20 minutes using an ultrasonic disperser; S2.6, cooling to below 40°C, adding the second photoinitiator and the remaining coupling agent, stirring for 5-10 minutes, and obtaining a second mixture; S2.7. Determine whether the viscosity is within the preset second viscosity range. If so, filter and degas in sequence to obtain the functional layer coating. If not, add a solvent to reduce the viscosity or add a thixotropic agent to increase the viscosity until the viscosity of the second mixture is within the preset second viscosity range.
[0012] In some embodiments of the present invention, step S4 includes: S4.1. Align the adhesive-backed copper foil and the substrate accurately and stack them so that the insulating layer is in contact with the substrate. Evacuate the pressure to -0.08 to -0.09 MPa. Apply a contact pressure of 0.1 to 0.3 MPa to the adhesive-backed copper foil and maintain the pressure for 10 to 12 minutes. S4.2, set the heating rate to 5~10℃ / min to 120~180℃, and keep it warm for 30~60min at a contact pressure of 0.3~1.0MPa; S4.3, after the heat preservation is completed, the temperature is slowly lowered to 40-60°C, the vacuum and pressure are released, and the copper layer of the adhesive-backed copper foil is etched, wherein the etching solution includes at least one of acidic copper chloride, alkaline copper chloride, and ferric chloride; S4.4. According to the required number of layers, vacuum bond another adhesive-backed copper foil to the etched copper layer, and repeat steps S4.2 and S4.3 to obtain a multi-layer circuit board.
[0013] Compared with the prior art, the processing method of a multi-layer circuit board in the present invention has the following beneficial effects: By splitting the coating into base layer coating and functional layer coating, the desired thickness of each layer can be optimized separately. When multiple layers need to be stacked, the same parameters can be maintained to obtain nearly consistent single-layer thickness in the same batch or different batches of production lines. This repeatability helps to ensure that the error accumulation of multi-layer boards in the Z direction (thickness direction) is smaller. Through segmented coating and thermal curing, stress can be controlled within a smaller range, and leveling can be performed during the vacuum bonding stage, significantly reducing dimensional deviations caused by internal stress, thereby improving the interlayer thickness uniformity and overall flatness of multi-layer circuit boards. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 The figure is a flow chart of a method for processing a multi-layer circuit board in one embodiment of the present invention. DETAILED DESCRIPTION
[0015] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0016] Please refer to Figure 1The present invention provides a method for processing a multi-layer circuit board, the steps comprising: S1. Surface treatment is performed on the copper foil raw material to obtain a roughened copper foil.
[0017] Step S1 includes: S1.1. Prepare a cleaning solution, which includes a weak alkaline solvent and a surfactant. The pH value of the cleaning solution is 9-11, for example, 9, 10, 11. Heat the cleaning solution to 40-60°C, for example, 40°C, 50°C, 60°C.
[0018] Weak alkaline solution removes grease and dirt. In an alkaline environment, grease and organic residues are saponified or emulsified and dispersed, which improves the surface cleanliness of the copper foil and creates a more uniform and undisturbed surface environment for the subsequent roughening step. By reducing the surface tension of the liquid, the cleaning liquid can fully contact the fine texture on the surface of the copper foil, accelerate the removal of oil and dirt, avoid stubborn dirt residue, and improve the overall cleanliness. The temperature is controlled at 40~60℃, and the chemical reaction rate is accelerated by moderate heating, while preventing the oxidation of the copper foil or unnecessary energy consumption caused by excessive temperature, so as to achieve a stable and controllable cleaning process.
[0019] The weak alkaline solvent includes at least one of sodium carbonate, ammonia water and triethanolamine, and the surfactant includes at least one of sodium lauryl sulfate, fatty alcohol polyoxyethylene ether and cocamidopropyl betaine.
[0020] S1.2. Circulate the cleaning solution, place the copper foil raw material in the cleaning solution, soak for 1 to 3 minutes, take it out, rinse it with pure water and then dry it.
[0021] Continuous rolling avoids dead corners or stagnant areas, allowing the cleaning liquid to fully contact the copper foil surface, effectively removing the detached oil and oxide scale, reducing secondary attachment, and improving cleaning uniformity. Multi-level or sufficient pure water rinsing removes residual alkali and surfactants to avoid subsequent local corrosion or dry spots caused by residual chemicals. This removes moisture in time, prevents secondary oxidation of the surface, and allows the copper foil to maintain a clean and stable surface state before entering the next acid roughening step.
[0022] S1.3, the dried copper foil raw material is placed in an acidic solution including sulfuric acid and chloride-containing salt, heated to 25-45°C for roughening, and maintained for 0.5-1.5 minutes. The roughened copper foil raw material is rinsed with multi-stage pure water and dried to obtain a roughened copper foil.
[0023] Sulfuric acid and an acidic solution containing chloride salts control the roughening time and temperature to produce uniform "micro-etching" or "concave-convex texture" on the surface of the copper foil, thereby increasing the surface roughness. Compared with the smooth copper surface that has not been roughened, it is easier to produce mechanical bite force with the subsequent coating layer or adhesive.
[0024] Multi-stage pure water rinsing completely removes residual acid and dissolved ions on the surface, prevents subsequent oxidation or corrosion, reduces the risk of surface defects caused by acid salt deposition, ensures that the coarsened texture is pure and free of impurities, and ensures that the coarsened texture maintains its morphology in a dry state and will not be passivated by moisture or chemical residues, providing a stable and repeatable surface reference for the next step (such as insulating paint coating and vacuum bonding).
[0025] S2. Prepare insulating coating, which includes base layer coating and functional layer coating.
[0026] In step S2, the base layer coating comprises a base resin, a crosslinking agent, a toughening agent, and a leveling agent. The base resin comprises at least one of epoxy resin, polyimide, and phenolic resin. The crosslinking agent comprises at least one of 4,4'-diaminodiphenylmethane, polyethylene polyamine, dicyandiamide, methyltetrahydrophthalic anhydride, maleic anhydride, methyl anhydride, and segmented urea-formaldehyde resin. The toughening agent comprises at least one of carboxyl-terminated nitrile rubber, polyether sulfone, and polyaryl sulfone. The functional layer coating includes functional resin, nano-composite filler, curing agent, and coupling aid. The functional resin includes at least one of amino / hydroxyl-containing epoxy resin, benzoxazine resin, and thermosetting acrylic copolymer resin. The nano-composite filler includes at least one of zinc oxide-graphene composite powder, aluminum oxide-carbon nanotube composite powder, silicon dioxide-graphene composite powder, and titanium dioxide-graphene composite powder. The curing agent includes at least one of 4,4'-diaminodiphenyl ether, methyl anhydride, and cyclohexylamine derivatives. The coupling aid includes at least one of γ-aminopropyltriethoxysilane, titanate coupling agent, and zirconate coupling agent.
[0027] The base layer coating also includes a first photoinitiator, which includes at least one of benzoin ether, 2-hydroxy-2-methyl-1-phenylpropanone, and 1-hydroxy-cyclohexylphenyl ketone. The functional layer coating also includes a second photoinitiator, which includes at least one of 2,4,6-trimethylbenzoyl) (dimethylamino) phenylphosphine oxide, (2-phenylpropionyl) triphenylphosphine oxide derivatives, and 2,4,6-trimethylbenzoyl diphenylphosphine oxide.
[0028] Step S2 includes: S2.1. Add solvent and base resin into the reaction tank, control the stirring temperature at 40-60°C, and keep stirring for 15-30 minutes.
[0029] The solvent can accelerate the dissolution of the base resin in the temperature range of 40~60℃, reduce the viscosity mutation or agglomeration phenomenon, and make the coating system easier to mix evenly when adding crosslinking agents and other ingredients later. Control the temperature at a moderate level (40~60℃) to avoid partial premature curing or performance loss of the resin due to overheating, and improve process controllability.
[0030] S2.2. When the viscosity of the system changes less than the preset range, add the cross-linking agent and stir for 5 to 10 minutes, then add the toughening agent and leveling agent and continue stirring for 10 to 15 minutes.
[0031] Monitor the viscosity curve first, and when the change is less than the preset range, add other components to ensure that the system reacts or blends in a relatively stable state to reduce unnecessary agglomeration or local solidification. The preset range can be set to ±5%.
[0032] Add the crosslinking agent after the resin is basically dispersed evenly to avoid uneven stirring due to too high or too low viscosity, and better control the initial stage of the crosslinking reaction. Toughening agents can improve the toughness of the final film, and leveling agents can improve the surface quality of the subsequent coating film. Adding them together at this stage allows them to disperse in the system as quickly as possible, reducing the mixing time of the secondary addition.
[0033] S2.3. The temperature is lowered to below 40°C, and the first photoinitiator is slowly added, and stirring is continued for 10 minutes to obtain a first mixture. The viscosity of the first mixture is controlled within the first viscosity range, and the first mixture is transferred to a vacuum degassing tank, maintained at -0.08MPa, and degassed for 5 to 10 minutes. After cooling to room temperature, the base layer coating is obtained.
[0034] Adding the photoinitiator after the temperature drops below 40°C can effectively prevent it from spontaneously decomposing or deactivating in a high temperature environment, ensuring that the subsequent photocuring reaction proceeds smoothly.
[0035] Controlling the viscosity in the first viscosity range helps to obtain the ideal film thickness and fluidity in the subsequent substrate coating process (such as slit coating or spraying). If the viscosity is too high, it is difficult to coat evenly, and if it is too low, it is easy to sag or difficult to form the required film thickness. The first viscosity range can be 100~300dPa·s.
[0036] Vacuum degassing and cooling are used to remove bubbles introduced by stirring to avoid subsequent defects such as bubbles and pinholes in the film. Lowering the temperature to room temperature can extend the storage period and prevent the resin from continuing to react or thicken.
[0037] S2.4. Ultrasonic disperse the nanocomposite raw material in a small amount of acetone or ethanol for 10 to 20 minutes, add part of the coupling agent, stir for 5 to 10 minutes, and dry at low temperature to obtain a nanocomposite filler.
[0038] Ultrasonic dispersion can effectively reduce the agglomeration of nanoparticles, increase the specific surface area, and make the subsequent contact with the resin system more complete. Adding coupling agents and stirring for a short time can make the filler surface react or combine with the additives, thereby improving its dispersion stability and interfacial bonding force in the subsequent functional resin. Controlling the drying temperature can avoid overheating that leads to degradation of nanomaterial performance or material agglomeration and reflux, and obtain nanopowders containing functional active groups, preparing for the subsequent functional layer resin mixing.
[0039] S2.5. Add functional resin and part of solvent into a stirring tank, heat to 50-60°C, add curing agent and stir for 10-15 minutes, slowly add nanocomposite filler into the stirring tank, and continue to disperse for 10-20 minutes using an ultrasonic disperser.
[0040] Preheating and stirring can reduce the viscosity of the system. The viscosity of functional resin is relatively lower at 50-60°C, which facilitates the mixing of nanofillers, reduces local agglomeration, and allows the curing agent to disperse more easily and fully contact the resin molecules.
[0041] Nanocomposite fillers are gradually added in combination with ultrasonic dispersion to avoid a large amount of one-time addition that may lead to a sharp increase in local viscosity or particle agglomeration. Ultrasonic dispersion again breaks up filler clusters to make the nanoparticles evenly distributed in the functional resin.
[0042] S2.6. Cool down to below 40°C, add the second photoinitiator and the remaining coupling agent, and stir for 5-10 minutes to obtain a second mixture.
[0043] Adding it at a lower temperature can prevent the photoinitiator from being destroyed or partially prematurely reacting in a high temperature environment. Supplementing the coupling agent can further enhance the interfacial bonding between the filler and the resin, improve the mechanical properties and corrosion resistance, and ensure the overall synergistic crosslinking of the functional layer during subsequent light / heat curing. The second mixture is mainly aimed at the functional layer coating formula, has the expected viscosity range, and can meet the needs of thicker films and long-wave UV curing.
[0044] S2.7. Determine whether the viscosity is within the preset second viscosity range. If so, filter and degas in sequence to obtain the functional layer coating. If not, add a solvent to reduce the viscosity or add a thixotropic agent to increase the viscosity until the viscosity of the second mixture is within the preset second viscosity range.
[0045] Based on precise control of online / offline viscosity detection, the viscosity can be quickly fine-tuned by adding solvents (dilution) or thixotropic agents (thickening), ensuring the rheological properties of coating and subsequent use processes, keeping the second mixture within the target coating window, and facilitating the formation of a uniform functional layer with controllable thickness. The second viscosity range can be 200~600dPa·s. The thixotropic agent includes at least one of fumed silica, organic bentonite, and modified polyamide wax. Fumed silica adsorbs each other through hydrogen bonds or van der Waals forces to form a three-dimensional network structure, which increases the viscosity of the system when it is stationary and decreases when subjected to shear force, thereby achieving a thixotropic effect; Filtration and degassing can remove possible large particles and bubbles, reduce subsequent coating defects, and ultimately ensure that the finished functional layer coating has good dispersion, low defect rate and stable light curing activity.
[0046] S3, sequentially coating at least one base layer coating and at least one functional layer coating on the rough surface of the roughened copper foil, performing a staged curing after each coating to form an insulating layer, and obtaining a self-adhesive copper foil, wherein the self-adhesive copper foil includes a copper layer connected to the insulating layer.
[0047] Step S3 includes: S3.1. Set the coating speed to 1-8 m / min, apply the base layer coating on the rough surface of the roughened copper foil, and control the gap accuracy between the lip of the coating head and the roughened copper foil to within 10-20 μm.
[0048] The copper foil is passed through the coating machine at a line speed of 1~8m / min to ensure that the base layer coating is evenly coated under continuous belt running conditions. At the same time, the gap accuracy between the lip of the coating head and the roughened copper foil surface is controlled within the range of 10~20μm to obtain the ideal base layer film thickness and flatness. By accurately controlling the size and travel speed during the coating process, it can ensure that the coating is evenly distributed on the entire substrate and achieve consistency in film thickness. Optimizing speed parameters can also improve production efficiency, while reducing the unevenness caused by the flow of the coating, and reducing the defects of the coating edge warping or local over-thickness or over-thinness.
[0049] The base layer coating is irradiated with a scanning light source with a wavelength of 365~385nm, a moving speed of 0.2~0.33m / s, a scanning power of 50~100mW / cm², and maintained for 30~120s.
[0050] After coating, the substrate coating is subjected to scanning light irradiation: wavelength 365~385nm, scanning power 50~100mW / cm²; scanning moving speed 0.2~0.33m / s, and irradiation is maintained for 30~120s. This allows the substrate surface to quickly form a gel or preliminary solidified shell layer to prevent excessive resin flow or film surface defects during subsequent thermal curing, while retaining some active groups to obtain good adhesion during subsequent stacking or lamination.
[0051] For the detection of coating thickness, laser interferometry / triangulation measurement can be used. The laser beam is used to illuminate the coating surface, and the distance between the coating and the substrate is calculated by measuring the phase difference or geometric displacement of the reflected light to obtain the coating thickness.
[0052] Or optical imaging and image processing, using a high-resolution camera to obtain a cross-sectional image of the coating, and using image processing algorithms to detect and measure the edge and calculate the film thickness. It is suitable for offline detection or as an auxiliary means of online monitoring, and can provide intuitive thickness distribution information.
[0053] Or ultrasonic thickness measurement, which sends ultrasonic pulses to the coating, measures its propagation time in the coating, and uses the speed of sound to calculate the coating thickness.
[0054] Alternatively, capacitive or infrared sensors use the dielectric constant or infrared transmittance characteristics of the coating material to estimate the coating thickness by measuring capacitance changes or infrared signal strength.
[0055] S3.2. Raise the temperature to 50~60℃, keep warm for 2~3min, then raise the temperature to 100~120℃, keep warm for 5~10min, and cool down to room temperature after heating.
[0056] Pre-bake at a lower temperature range to allow residual solvents or a small amount of volatile components to escape smoothly and avoid bubbles or surface crusting. At this time, the photocured surface of the substrate layer will be further consolidated and the viscosity will gradually rise to a semi-cured level.
[0057] Short-term curing in the medium and high temperature zone allows the base layer resin to undergo more complete cross-linking. The time to maintain this temperature range is determined by the resin formula, and 5 to 10 minutes is sufficient to meet the initial film formation and strength requirements.
[0058] After cooling to room temperature, the base layer coating is in a stable semi-cured state, the surface hardness is improved, and good interface bite can be ensured when it is bonded with the subsequent functional layer coating.
[0059] S3.3. An ultrasonic dispersing unit is arranged in front of the coating head to disperse the functional layer coating while conveying it, and the functional layer coating is coated on the surface of the cured base layer coating, and the thickness of the functional layer coating is controlled to be 30~50μm.
[0060] An ultrasonic dispersion module is set at the front end of the coating head to continuously redisperse the functional layer coating (containing nanocomposite fillers) to ensure that the fillers do not aggregate and the concentration is uniform during the flow process. The functional layer coating is applied to the surface of the cured substrate layer to maintain a wet film thickness of 30~50μm (which can be achieved through the coating head gap or metering pump speed control).
[0061] The functional layer coating is irradiated with a light source having a wavelength of 405-420 nm and a power of 200-300 mW / cm² for 5-10 seconds.
[0062] The functional layer formula contains long-wavelength photoinitiator, which is suitable for subsequent 405~420nm UV irradiation and thermal curing. Rapid deep gelation or surface drying treatment is carried out to ensure that the functional layer does not flow in a large range during subsequent thermal curing, and the internal nanofiller forms a stable three-dimensional network structure in the resin.
[0063] In one embodiment, the coating head can use a dual coating head system to separately coat the base layer coating and the functional layer coating. The dual coating head system refers to a technical configuration in which two independent coating heads are used in the coating process to apply the coating to the substrate in a synchronous or continuous manner. The system can simultaneously apply the base layer coating and the functional layer coating to different areas of the same substrate or continuously at the same position, thereby forming a double-layer or multi-layer structure.
[0064] Through the collaborative operation of two coating heads, the local flow fluctuations or uneven thickness problems that may exist in a single coating head can be corrected more effectively, thereby achieving uniform distribution and consistency of the overall coating. The dual coating head system can quickly apply the functional layer coating when the base layer coating is still in a semi-cured state, forming better mechanical bite and chemical bonding, and improving the interlayer bonding strength of the final product. Through parallel or continuous dual-head coating, the coating and curing time of a single coating can be shortened, the output speed of the entire production line can be increased, and the process cycle can be reduced. The dual coating head design is usually combined with a precision control system to monitor and adjust the coating parameters (such as flow rate, coating gap, etc.) in real time, so as to stabilize the coating quality and reduce the defective rate. The system can integrate online detection equipment to achieve real-time monitoring of the thickness and uniformity of each coating, which is convenient for timely adjustment of process parameters to ensure that the final product meets the design requirements.
[0065] S3.4. Heat to 120~140℃, keep warm for 10~30min, and cool to room temperature after heating.
[0066] The functional layer is thermally cured more thoroughly in a higher temperature zone, so that the crosslinking degree of each component (functional resin, nanofiller interface, photoinitiator, etc.) reaches the expected level, and the interface bonding between the substrate layer and the functional layer is further strengthened. After the functional layer is cured, the temperature drops to form a high-density, high-adhesion multifunctional insulating coating.
[0067] Prolonging the heat preservation time of the coating, that is, prolonging the leveling time, gives the leveling agent enough time to play a role in the coating, promoting the self-flow and leveling of the coating, thereby eliminating tiny bumps and unevenness. Ultimately, a smoother and more uniform coating film can be obtained, improving the appearance and physical properties of the product and reducing the risk of stress concentration in subsequent processes.
[0068] S3.5, repeating steps S3.1 to S3.4 according to the preset number of layers to form an insulating layer and obtain a copper foil with adhesive backing.
[0069] If a higher thickness or multiple properties are required (such as the second functional layer, the third functional layer, etc.), S3.1~S3.4 can be repeated: each layer uses short-wave UV to lock the base layer first, and long-wave UV to quickly cure the functional layer, combined with staged thermal curing. After the multi-layer coating is cured, the copper foil has a high-strength, high-barrier insulation layer. The adhesive-backed copper foil can be bonded to the substrate in the subsequent lamination process to achieve a firm bond, and can be directly etched to form the outer layer circuit pattern.
[0070] In one embodiment, the adhesive copper foil is wound in a tension control system, which includes a plurality of roller shafts that can be adjusted up and down, and the distance between the roller shafts is controlled to control the tension of the adhesive copper foil, so as to ensure that the adhesive copper foil maintains a stable tension in each process and prevent the material from deforming, curling or warping. This helps to improve the uniformity and dimensional accuracy of the coating, while ensuring the alignment accuracy of the multi-layer structure and the overall quality of the final product.
[0071] In one embodiment, the coating system uses a continuous supply process for insulating coating to achieve a stable and continuous supply of coating raw materials, avoiding composition fluctuations and rheological property changes caused by batch addition or intermittent feeding. This not only ensures the uniformity of the coating formula, but also reduces the risk of coating defects caused by unstable ratios, and improves process controllability and product consistency.
[0072] S4. Vacuum-bond the insulating layer of the adhesive-backed copper foil to the substrate, etch the copper layer to form a conductive circuit, and repeat the bonding and etching steps of at least one adhesive-backed copper foil within the required number of layers to obtain a multi-layer circuit board.
[0073] Step S4 includes: S4.1. Align and stack the adhesive-backed copper foil and substrate precisely so that the insulating layer contacts the substrate. Evacuate to -0.08~-0.09MPa and apply a contact pressure of 0.1~0.3MPa to the adhesive-backed copper foil for 10~12min.
[0074] After alignment and positioning, the adhesive-backed copper foil (insulating layer) is tightly attached to the substrate surface to ensure that the line position error is minimized during subsequent lamination or stacking interconnection, avoid poor conduction or overlap caused by misalignment, and improve the overall accuracy of the multilayer board.
[0075] Vacuuming can remove air between interfaces and recesses to prevent bubbles or voids from being generated during subsequent heating or pressurization, significantly improving bonding integrity and interlayer adhesion, and reducing potential delamination or dielectric defects caused by air gaps.
[0076] First, perform preliminary bonding with relatively low pressure to make the adhesive-backed copper foil fully adhere to the substrate surface under vacuum to avoid excessive glue flow or displacement due to excessive pressure. Maintaining it for 10 to 12 minutes can allow the insulating layer to soften appropriately and fully contact the microscopic surface of the substrate, further improving the quality of subsequent lamination.
[0077] S4.2. Set the heating rate to 5-10°C / min to 120-180°C and keep it warm for 30-60 min at a contact pressure of 0.3-1.0 MPa.
[0078] Gradual heating can better manage resin fluidity and internal stress release, avoid local stress concentration caused by sudden temperature rise, too fast resin curing or bubble trapping, and cooperate with the vacuum state to make the discharge of solvent or residual gas smoother.
[0079] Fully thermally cure in this temperature range allows the resin in the adhesive-backed copper foil (whether in B-stage or partially cured state) to achieve final cross-linking after bonding with the substrate. The contact pressure of 0.3~1.0MPa can promote the flow of resin at the microscopic level, fill gaps and form a strong interface bond, thereby improving the mechanical strength and durability of the laminate.
[0080] After sufficient curing, the insulating layer and the substrate become one, and the bonding strength is significantly improved, laying a solid foundation for subsequent circuit etching and multi-layer stacking, and improving the overall reliability and service life of the multi-layer circuit board.
[0081] S4.3. After the heat preservation is completed, the temperature is slowly lowered to 40-60°C, the vacuum and pressure are released, and the copper layer of the adhesive-backed copper foil is etched, and the etching solution includes at least one of acidic copper chloride, alkaline copper chloride, and ferric chloride.
[0082] After the insulation is completed, the temperature is gradually reduced to 40~60℃ before releasing the vacuum and pressure. This can avoid thermal stress or local warping and cracking caused by sudden cooling, minimize the internal stress of the resin / substrate interface, and improve the interlayer stability.
[0083] Once the internal and external temperatures of the board are close, the internal stress difference is reduced, the vacuum and external pressure are released so that the entire laminate is under normal pressure, reducing operational risks and ensuring that the bonding quality meets the standards.
[0084] Acidic copper chloride, alkaline copper chloride or ferric chloride is used to remove the outer copper layer from the designated area to form a predetermined circuit pattern. The type of etching solution can be selected according to different requirements such as circuit resolution and etching rate, taking into account both efficiency and precision.
[0085] S4.4. According to the required number of layers, another adhesive-backed copper foil is vacuum-bonded to the etched copper layer, and steps S4.2 and S4.3 are repeated to obtain a multi-layer circuit board.
[0086] If more layers are needed, after the circuit pattern of the previous layer has been completed, a new adhesive-backed copper foil can be attached and the curing and etching processes can be repeated to achieve a multi-layer circuit board structure layout with 3, 4, 6 or even more layers to meet the needs of high-density interconnection.
[0087] After each etching, a new conductive circuit layer will be left, and then the adhesive-backed copper foil will be attached to it to form the next insulating layer. Various structures such as blind holes can be freely designed to meet the requirements of fine wiring and complex routing.
[0088] The dense insulating layer of the adhesive-backed copper foil is organically combined with the circuit formed by multi-layer etching to obtain a low-porosity, high-reliability multi-layer board with excellent electrical insulation, corrosion resistance and mechanical reliability, thus meeting the needs of demanding applications such as high-speed communications, automotive electronics, military and aerospace.
[0089] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for processing a multi-layer circuit board, characterized in that the steps include: S1. Surface treating the copper foil raw material to obtain a roughened copper foil; S2. preparing an insulating coating, wherein the insulating coating comprises a base layer coating and a functional layer coating; S3, sequentially coating at least one of the base layer coating and at least one of the functional layer coating on the rough surface of the roughened copper foil, performing a staged curing after each coating to form an insulating layer, and obtaining a self-adhesive copper foil, wherein the self-adhesive copper foil includes a copper layer connected to the insulating layer; S4, vacuum-bonding the insulating layer of the adhesive-backed copper foil to the substrate, etching the copper layer to form a conductive circuit, and repeating at least one adhesive-backed copper foil bonding and etching step within the required number of layers to obtain a multi-layer circuit board.
2. The method for processing a multi-layer circuit board according to claim 1, characterized in that: The step S1 comprises: S1.1, prepare a cleaning solution, the cleaning solution includes a weak alkaline solvent and a surfactant, the pH value of the cleaning solution is 9-11, and the cleaning solution is heated to 40-60°C; S1.
2. Circulate the cleaning solution, place the copper foil raw material in the cleaning solution, soak for 1 to 3 minutes, take it out, rinse it with pure water and then dry it; S1.3, the dried copper foil raw material is placed in an acidic solution including sulfuric acid and chloride-containing salt, heated to 25-45°C for roughening, and maintained for 0.5-1.5 minutes. The roughened copper foil raw material is rinsed with multi-stage pure water and dried to obtain a roughened copper foil.
3. The method for processing a multi-layer circuit board according to claim 1, characterized in that: In the step S2, the base layer coating comprises a base resin, a crosslinking agent, a toughening agent, and a leveling agent. The base resin comprises at least one of epoxy resin, polyimide, and phenolic resin. The crosslinking agent comprises at least one of 4,4'-diaminodiphenylmethane, polyethylene polyamine, dicyandiamide, methyltetrahydrophthalic anhydride, maleic anhydride, methyl anhydride, and segmented urea-formaldehyde resin. The toughening agent comprises at least one of carboxyl-terminated nitrile rubber, polyether sulfone, and polyaryl sulfone. The functional layer coating comprises a functional resin, a nano-composite filler, a curing agent, and a coupling aid. The functional resin comprises at least one of an epoxy resin containing amino / hydroxyl groups, a benzoxazine resin, and a thermosetting acrylic copolymer resin. The nano-composite filler comprises at least one of a zinc oxide-graphene composite powder, an aluminum oxide-carbon nanotube composite powder, a silicon dioxide-graphene composite powder, and a titanium dioxide-graphene composite powder. The curing agent comprises at least one of 4,4'-diaminodiphenyl ether, methyl anhydride, and a cyclohexylamine derivative. The coupling aid comprises at least one of γ-aminopropyltriethoxysilane, a titanate coupling agent, and a zirconate coupling agent.
4. The method for processing a multi-layer circuit board according to claim 1, characterized in that: The step S3 comprises: S3.1, setting the coating speed to 1-8 m / min, coating the base layer coating on the rough surface of the roughened copper foil, and controlling the gap accuracy between the lip of the coating head and the roughened copper foil to be within 10-20 μm; S3.2, heat to 50~60℃, keep warm for 2~3min, then heat to 100~120℃, keep warm for 5~10min, and cool to room temperature after heating; S3.3, an ultrasonic dispersing unit is arranged in front of the coating head to disperse the functional layer coating while conveying, and the functional layer coating is coated on the surface of the cured base layer coating, and the thickness of the functional layer coating is controlled to be 30-50 μm; S3.4, heat to 120~140℃, keep warm for 10~30min, and cool to room temperature after heating; S3.5, repeating steps S3.1 to S3.4 according to the preset number of layers to form an insulating layer and obtain a copper foil with adhesive backing.
5. The method for processing a multi-layer circuit board according to claim 4, characterized in that: The base layer coating comprises a first photoinitiator, the functional layer coating comprises a second photoinitiator, and before step S3.2, further comprising: The base layer coating is irradiated with a scanning light source with a wavelength of 365-385 nm, a moving speed of 0.2-0.33 m / s, a scanning power of 50-100 mW / cm², and maintained for 30-120 seconds; Before step S3.4, the method further includes: The functional layer coating is irradiated with a light source having a wavelength of 405-420 nm and a power of 200-300 mW / cm² for 5-10 seconds.
6. The method for processing a multi-layer circuit board according to claim 5, characterized in that: The first photoinitiator includes at least one of benzoin ether, 2-hydroxy-2-methyl-1-phenylpropanone, and 1-hydroxy-cyclohexyl phenyl ketone, and the second photoinitiator includes at least one of 2,4,6-trimethylbenzoyl (dimethylamino) phenyl phosphine oxide, a (2-phenylpropionyl) triphenyl phosphine oxide derivative, and 2,4,6-trimethylbenzoyl diphenyl phosphine oxide.
7. The method for processing a multi-layer circuit board according to claim 5, characterized in that: The step S2 comprises: S2.
1. Add solvent and base resin into the reaction tank, control the stirring temperature at 40-60°C, and keep stirring for 15-30 minutes; S2.2, after the viscosity of the system changes less than the preset range, add the crosslinking agent, stir for 5-10 minutes, then add the toughening agent and leveling agent, and continue stirring for 10-15 minutes; S2.3, the temperature is lowered to below 40°C, the first photoinitiator is slowly added, and stirring is continued for 10 minutes to obtain a first mixture, the viscosity of the first mixture is controlled within the first viscosity range, the first mixture is transferred to a vacuum degassing tank, maintained at -0.08MPa, degassed for 5 to 10 minutes, and the base layer coating is obtained after cooling to room temperature; S2.4, ultrasonically disperse the nanocomposite raw material in a small amount of acetone or ethanol for 10 to 20 minutes, add part of the coupling agent, stir for 5 to 10 minutes, and dry at low temperature to obtain a nanocomposite filler; S2.5, adding functional resin and part of solvent into a stirring tank, heating to 50-60°C, adding curing agent and stirring for 10-15 minutes, slowly adding the nanocomposite filler into the stirring tank, and continuously dispersing for 10-20 minutes using an ultrasonic disperser; S2.6, cooling to below 40°C, adding the second photoinitiator and the remaining coupling agent, stirring for 5-10 minutes, to obtain a second mixture; S2.
7. Determine whether the viscosity is within the preset second viscosity range. If so, filter and degas in sequence to obtain the functional layer coating. If not, add a solvent to reduce the viscosity or add a thixotropic agent to increase the viscosity until the viscosity of the second mixture is within the preset second viscosity range.
8. The method for processing a multi-layer circuit board according to claim 1, characterized in that: The step S4 comprises: S4.
1. Align the adhesive-backed copper foil and the substrate accurately and stack them so that the insulating layer is in contact with the substrate. Evacuate the pressure to -0.08 to -0.09 MPa. Apply a contact pressure of 0.1 to 0.3 MPa to the adhesive-backed copper foil and maintain the pressure for 10 to 12 minutes. S4.2, set the heating rate to 5~10℃ / min to 120~180℃, and keep it warm for 30~60min at a contact pressure of 0.3~1.0MPa; S4.3, after the heat preservation is completed, the temperature is slowly lowered to 40-60°C, the vacuum and pressure are released, and the copper layer of the adhesive-backed copper foil is etched, wherein the etching solution includes at least one of acidic copper chloride, alkaline copper chloride, and ferric chloride; S4.
4. According to the required number of layers, vacuum bond another adhesive-backed copper foil to the etched copper layer, and repeat steps S4.2 and S4.3 to obtain a multi-layer circuit board.